2019
DOI: 10.1111/fcp.12501
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of metformin on a rat model of lipopolysaccharide‐induced preeclampsia

Abstract: Recent in vitro and clinical studies have found that metformin (MET) may play a preventive or therapeutic role in preeclampsia (PE) and may be a candidate drug for the prevention and/or treatment of PE. In this study, we used lipopolysaccharide (LPS) to induce a PE‐like rat model and investigated the intervention effect of MET from the perspectives of clinical manifestations, placental morphology, serum marker for placental injury, systemic inflammatory response and oxidative/nitrative stress, and placental nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 61 publications
1
22
0
1
Order By: Relevance
“…Apart from type 2 diabetes, metformin is also used to prevent or delay the onset of diabetes in subjects at high risk for this disease [21,22]. Prediabetes is an intermediate state of hyperglycemia with glycemic parameters above normal but below the diabetes threshold, reflecting the presence of either, or both, impaired fasting glucose and impaired glucose tolerance [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from type 2 diabetes, metformin is also used to prevent or delay the onset of diabetes in subjects at high risk for this disease [21,22]. Prediabetes is an intermediate state of hyperglycemia with glycemic parameters above normal but below the diabetes threshold, reflecting the presence of either, or both, impaired fasting glucose and impaired glucose tolerance [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Microglia are encephalic cells that are local macrophages of the central nervous system and play an essential role in cerebral immune function. Microglial inflammation induced pro‐inflammatory cytokines and pro‐inflammatory enzymes expression , thus resulting in inflammation‐induced neuronal cell death. Recently, increased intracellular glycolysis was indicated to participate in LPS‐mediated immune cells and microglia inflammation .…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in a normalization of blood pressure, reduced proteinuria, improvement in fetal growth, and decreased stillbirth frequency. The authors concluded that metformin is beneficial to the PE-like rat model by protecting placentas from injury; thus, it could be an attractive agent for PE prevention and/or treatment [123]. It has been reported that the decrease in IL-27, TNF-α, and IL-6 expression in vivo (in both preeclamptic rat models and trophoblast cells) was the result of H19 inhibition by metformin in a dose-dependent manner [124].…”
Section: Impact On Preeclampsia Pathophysiologymentioning
confidence: 99%